Citizens here and there against the crisis: immigrant organizations’ transnational solidarity during the COVID-19 pandemic - Artero, Maurizio (Frontiers in Sociology, 2025)
This article examines the solidarity initiatives undertaken by immigrant organizations in Italy during the COVID-19 pandemic, highlighting the significance of a transnational perspective in understanding these efforts. Drawing on two qualitative studies, particularly the analysis of 19 interviews with leaders of Italian immigrant organizations involved in solidarity work during the pandemic, the findings highlight that solidarity extends beyond co-ethnic support to encompass broader community engagement, especially in times of crisis. Indeed, the study reveals how immigrant organizations mobilized resources for both their home countries and the host society, demonstrating a commitment to collective wellbeing that transcends national boundaries. This article contributes to the discourse on transnational citizenship, revealing how immigrants enact substantive citizenship through participation in social initiatives that address urgent needs.